Pemberian Makanan Tambahan dan Edukasi Gizi Seimbang Dalam Rangka Penanganan Balita Stunting di Kelurahan Oesapa Selatan Kota Kupang - Yohanes Don Bosko Demu,; Astuti Nur, (Joong-Ki : Jurnal Pengabdian Masyarakat, 2023)
This Community Service aims to play a role in preventing and handling stunting through the Stunting Child Foster Parent Program (OTA2S) by providing additional food and providing balanced nutrition education for stunted and malnourished toddlers, increasing nutritional knowledge of mothers of toddlers in providing food to toddlers. . Providing food to stunted and malnourished toddlers for 90 days. Before administration, an initial weight measurement is carried out and every month monitoring and evaluation is carried out for children under five who are stunted and malnourished. As a result of community service, there was an increase in the knowledge of parents of toddlers in providing food to their children. However, there was no increase in weight, height and LILA because the children were in an unhealthy condition.